Impact of HPV Catch-Up Vaccination on High-Grade Cervical Lesions (CIN2+) Among Women Aged 26–30 in Northern Norway - Amanda Sørensen Jørgensen; Gunnar Skov Simonsen; Sveinung Wergeland Sørbye (Vaccines)
Background/Objectives: Human papillomavirus (HPV) is the primary cause of high-grade cervical lesions and cervical cancer worldwide. In Norway, HPV vaccination was introduced in 2009 for seventh-grade girls and extended through a catch-up program from 2016 to 2019 for women born between 1991 and 1996. This study evaluates the impact of the catch-up vaccination program on the incidence of HPV and high-grade cervical lesions in Troms and Finnmark. Methods: We analyzed data from 40,617 women aged 26 to 30 who underwent cervical screening between 2009 and 2023 in Troms and Finnmark, including 1850 women with high-grade cervical lesions (CIN2+) on biopsy. Using linear regression, we assessed trends in high-grade lesion incidence per 1000 screened women and the association between vaccination status and HPV-16/18 incidence. Results: Between 2017 and 2023, the incidence of high-grade cervical lesions significantly decreased: CIN2+ decreased by 33.4%, and CIN3+ decreased by 63.4%. Significant reductions in HPV-16/18-associated high-grade cervical lesions were observed among vaccinated women, with the proportion of CIN2+ cases due to HPV-16 and 18 decreasing from 56.8% in 2017 to 40.7% in 2023, reflecting a 55.8% reduction in the absolute number of cases caused by these high-risk HPV types. Comparing unvaccinated women aged 25–26 in 2016 and vaccinated women in 2023, HPV-16 incidence decreased from 5.1% to 0.1%, and HPV-18 incidence decreased from 3.3% to 0.0%. Conclusions: The catch-up vaccination program significantly reduced the incidence of HPV-16/18 and high-grade cervical lesions in Troms and Finnmark, even with the lower vaccination coverage observed in the catch-up program. These findings demonstrate the effectiveness of HPV vaccination programs in reducing HPV infections and associated cervical lesions.